Feeding Bugs to Bugs: Edible Insects Modify the Human Gut Microbiome in an in vitro Fermentation Model - Young, Wayne; Arojju, Sai Krishna; McNeill, Mark R.; Rettedal, Elizabeth; Gathercole, Jessica; Bell, Nigel; Payne, Penny (Frontiers in Microbiology, 2020)
We here report a study characterising the potential for edible insects to act as a prebiotic by altering the bacterial composition of the human faecal microbiome, using batch cultures inoculated with faecal adult human donors. Black field cricket nymphs, grass grub larvae, and wax moth larvae were subjected to an in vitro digestion to simulate the oral, gastric, and small intestinal stages of digestion. The digested material was then dialysed to remove small molecules such as amino acids and free sugars to simulate removal of nutrients through upper gastrointestinal tract digestion. The retentate, representing the digestion resistant constituents, was then fermented in faecal batch cultures for 4h, 7h, and 15h to represent rapid and longer fermentation times. Batch cultures without any added substrates were also set up to act as controls. Additionally, phosphate-buffered saline was used as a no-protein control and milk powder as “standard” protein control. At the end of the incubation period, the bacterial pellets were collected for microbiome analysis by 16S rRNA gene amplicon sequencing. Analysis of faecal cultures showed striking differences in community composition. Each substrate led to significant differences across a wide range of taxa compared to each other and PBS controls. Among the differences observed, digested grass grub larvae increased proportions of Faecalibacterium and the Prevotella 2 group. Black field crickets increased the prevalence of the Escherichia-Shigella group, Dialister genus, and a group of unclassified Lachnospiraceae. Wax moth larvae promoted the expansion of the same group of unclassified Lachnospiraceae and the Escherichia/Shigella group. The increased Faecalibacterium observed in the cultures with grass grub larvae represents a noteworthy finding as this bacterium is widely thought to be beneficial in nature, with demonstrated anti-inflammatory properties and associations with gut health. We conclude that insects can differentially modulate the microbiome composition in batch cultures inoculated with adult faecal material after simulated in vitro digestion. Although the physiological impact in vivo remains to be determined, this study provides sound scientific evidence that investigating the potential for consuming insects for gut health is warranted.